Merasa aman karena dianggap normal, kemudahan dan kepasrahan sebagai alasan ibu-ibu memilih persalinan rumah di desa: Studi Kualitatif di Kalimantan Tengah - Aderi Aderi; Yayi Suryo Prabandari; Atik Triratnawati (Berita Kedokteran Masyarakat (BKM), 2016)
Feeling safe due to normal antenatal care, easier to going to health facility, and compliance to God decision as reasons for home delivery choice among village mothers: a qualitative study in Central KalimantanPurposeThe purpose of this paper was to explore mothers’ perceptions of delivery at home in Kartika Bhakti Village, Province of Central Kalimantan. MethodsA case study was conducted involving observations, in-depth interviews and focus group discussion with 7 maternity women, 1 maternity women’s husbands, 1 village midwife, 1 community leader and 1 midwife of the village health post in Kartika Bhakti village, Province of Central Kalimantan.ResultsThe study found six reasons why mothers tended to choose to do delivery at home: barriers to delivery at health facilities; attitudes and preparedness of the midwife to deliver home deliveries; delivery at home benefits; based on the results of the pregnancy examination; not afraid of the risks of delivery; and ready to accept the dangers and risks of delivery.ConclusionThe reasons will be used as a consideration for choosing the birthplace. When the results of a pregnancy examination is good, mothers will tend to choose a home delivery. Furthermore, obstacles in health facilities such as barriers in health centers, geographical, hospital barriers, no postpartum services, and economic abilities are also some of the main reasons to choose to deliver at home. Health education and approaches related to delivery safety need to be improved to change mothers’ perceptions.